Hubungan antara Motivasi Belajar dengan Minat Belajar Warga Binaan pada Keterampilan Menjahit di Panti Sosial Karya Wanita Andam Dewi Solok - Arion Nopaldi; Setiawati Setiawati (Universitas Negeri Padang, 2018)
This research was motivated by the low level of learning interest of inmates in participating in skill activities at the Andam Dewi Solok Women's Social Workers' Organization (PSKW). This study aims to: 1) to describe learning motivation in sewing skills for inmates in PSKW Andam Dewi Solok, 2) to describe the learning interest in sewing skills for inmates in PSKW Andam Dewi Solok, 3) to see the relationship between learning motivation and interest in learning inmates following sewing skills in PSKW Andam Dewi Solok. This research includes correlational quantitative research. The population in this study were 40 people. The stratified random sampling technique was taken as many as 75% of the inmates. The number of samples in this study were 30 inmates. Data collection techniques used are questionnaires, while data collection tools use questionnaires. Data analysis techniques use percentages and product moments. From the results of the study, it can be seen that (1) the learning motivation of inmates in sewing skills activities is categorized as low, (2) learning interest of inmates in participating in sewing skills is categorized as low, and (3) there significant relationship between learning motivation and learning interest of inmates in participating in sewing skills activities. Keywords: Learning Motivation, Sewing Skills, Interest in Learning, Sex Worker (PSK)